Upaya Peningkatan Keaktifan Peserta Didik Kelas VIII A SMP Muhammadiyah 1 Godean Menggunakan Model Guided Discovery Learning - Anggita Yekti Fathoni (Universitas Muhammadiyah Gresik, 2021)
This research study aimed to find out the improvement of the students’ activeness of grade VIII-A of SMP Muhammadiyah 1 Godean through the implementation of the guided discovery learning model. The subjects of this action research were 32 students of grade VIII-A of SMP Muhammadiyah 1 Godean. The data were obtained through observation which was conducted in three research cycles. It was conducted from October 23rd to November 3rd, 2020. The data were analyzed using the calculation of the indicator percentage of the students’ activeness which appeared. The result of the research study showed that in the three learning cycles using the guided discovery learning model, the students’ activeness of grade VIII-A of SMP Muhammadiyah 1 Godean improved. The percentage of the students’ activeness for each cycles achieved 46,11%, 47,31%, and 58,06%.